Pengangkatan Anak sebagai Jalan Keluar Konflik Keluarga: Penelitian - Mezi Watdila Idfi; Shandra Puspita Dewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This paper discusses how the husband and wife avoid or overcome the conflicts that exist in their family. And why is tabbani a solution to family problems that occur. The research method in this paper is to use field research, carried out directly in the field against the background of the current situation. This paper uses a qualitative approach. Data collection techniques in this paper are interviews and literature studies. The data analysis technique in this paper is a qualitative data analysis technique in which the process of collecting data is through records and notes, literature review, interviews, surveys or observation. The conclusion of this research is that children are a gift and a great trust from the Almighty to husband and wife who can provide new happiness in the family. The presence of children is eagerly awaited by every married couple. But not infrequently there are still many couples who do not have children. So every couple needs to do something positive and find a way out, one of which is by adopting a child (tabbani). Then maintain a sense of mutual love and create good communication in order to create happiness and harmony in the family.